Analisis Determinan Stunting Pada Balita 2-5 Tahun Di Puskesmas Kassi-Kassi Makassar - Rizky Fitriyati Baharuddin; Fatmah Afrianty Gobel; Nur Ulmy Mahmud; Nurul Ulfah Mutthalib; Farihah Muhsanah (Window of Public Health Journal, 2025)
Based on the 2018 Riskesdas data, the prevalence of stunting in South Sulawesi was 35%. The latest data from the Makassar City Health Office shows the presentation of toddlers suffering from stunting in various Makassar City Health Centers, with the highest prevalence ranking being the Barrang Lompo Health Center at 34.77%, the second-ranking being the Kassi-Kassi Health Center at 22.92%. The third-ranking is the Kaluku Bodoa Health Center, at 18.47%. The prevalence of stunting in Makassar City is still far below the 20% standard set by the World Health Organization. This study, which aims to determine the risk factors for LBW, maternal education level, history of exclusive breastfeeding, and family income with the incidence of stunting in toddlers aged 2-5 years at the Kassi-Kassi Health Center Makassar in 2024, was conducted using a quantitative analytical research method with a case-control approach. The population in this study were all toddlers aged 2-5 years in the Kassi-Kassi Health Center Makassar. The sampling technique in this study was a non-probability sampling technique using a purposive sampling method with a sample size of 144 respondents. The data analysis method used univariate and bivariate tests with Odds Ratio (OR) calculations. The results of the study showed that LBW (OR = 0.049; 95% CI 0.014-0.178), history of exclusive breastfeeding (OR = 0.055; 95% CI 0.019-0.159), and family income (OR = 0.038; 95% CI 0.015-0.095) were protective factors for stunting. Meanwhile, maternal education level (OR = 1.109; 95% CI 0.511-2.404) was not a risk factor for stunting in toddlers aged 2-5 years in the Kassi-Kassi Health Center work area of ​​Makassar City in 2024.